T-type Ca Channel Blockers in Patients with Chronic Kidney Disease in Clinical Practice - Abe, Masanori; Okada, Kazuyoshi; Soma, Masayoshi (Current Hypertension Reviews, 2013)
Chronic kidney disease (CKD) progressively increases the risk of cardiovascular disease (CVD) and end-stage renal disease (ESRD) in line with its severity. Recent studies have revealed that albuminuria and proteinuria in CKD are risk factors for both ESRD and CVD. Accordingly, reductions in albuminuria and proteinuria are associated with a trend in reduced renal death and cardiovascular events. Renin-angiotensin-aldosterone system inhibitors, including angiotensin converting enzyme inhibitors and angiotensin II receptor blockers are recommended as first-choice drugs for the treatment of hypertensive patients with CKD according to several guidelines. However, monotherapy is not sufficient to control blood pressure, particularly in patients with CKD, highlighting the need for combination drug therapy. Calcium channel blockers (CCBs) reduce blood pressure and are useful antihypertensive drugs. Three types of CCBs––the L-, T-, and Ntypes–– are in clinical use. In renal tissue, L-type calcium channels are present only in the afferent arterioles, while N-type and T-type calcium channels are located in both efferent and afferent arterioles. Therefore, CCBs that block either T-type or N-type calcium channels may exert renoprotective effects by dilating the efferent artery and protecting the glomerulus from hyperfiltration injury. It has been established that T-type CCBs exert a renal protective action by ameliorating glomerular microcirculation via vasodilatory activity on both afferent and efferent arterioles. Additionally, blockade of the T-type Ca channel suppresses inflammatory processes, renin-angiotensin-aldosterone system, and oxidative stress. Such effects of T-type CCBs seem to provide good efficacy in terms of the progression of renal outcome and the prevention of cardiovascular events in patients with CKD.
Keywords: hypertension